2017
DOI: 10.1371/journal.pone.0183058
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stressors and the potential for synergistic loss of New England salt marshes

Abstract: Climate change and other anthropogenic stressors are converging on coastal ecosystems worldwide. Understanding how these stressors interact to affect ecosystem structure and function has immediate implications for coastal planning, however few studies quantify stressor interactions. We examined past and potential future interactions between two leading stressors on New England salt marshes: sea-level rise and marsh crab (Sesarma reticulatum) grazing driven low marsh die-off. Geospatial analyses reveal that cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Sea-level rise has already been linked to an intra-marsh Uca range expansion ( Luk & Zajac, 2013 ), and it can directly cause creekbank vegetation loss in the absence of crab impacts ( Schultz, Anisfeld & Hill, 2016 ). These multiple lines of evidence agree with recent findings across southern New England ( Schultz, Anisfeld & Hill, 2016 ; Crotty, Angelini & Bertness, 2017 ) and identify sea-level rise as a potential driver of creekbank vegetation loss in RI, either directly through inundation stress or indirectly via enhanced crab abundance and impacts.…”
Section: Discussionsupporting
confidence: 88%
“…Sea-level rise has already been linked to an intra-marsh Uca range expansion ( Luk & Zajac, 2013 ), and it can directly cause creekbank vegetation loss in the absence of crab impacts ( Schultz, Anisfeld & Hill, 2016 ). These multiple lines of evidence agree with recent findings across southern New England ( Schultz, Anisfeld & Hill, 2016 ; Crotty, Angelini & Bertness, 2017 ) and identify sea-level rise as a potential driver of creekbank vegetation loss in RI, either directly through inundation stress or indirectly via enhanced crab abundance and impacts.…”
Section: Discussionsupporting
confidence: 88%
“…Luk and Zajac (2013) suggested that landward expansion of low marsh vegetation species may facilitate increased distribution of fiddler crabs. Likewise, Crotty et al (2017) indicated the potential interaction between future SLR and Sesarma reticulatum impacts on marshes, as did Raposa et al (2018b) based on increases in crab burrows during recent periods of higher water levels. Likewise, Crotty et al (2017) indicated the potential interaction between future SLR and Sesarma reticulatum impacts on marshes, as did Raposa et al (2018b) based on increases in crab burrows during recent periods of higher water levels.…”
Section: Crabs and Sea-level Risementioning
confidence: 97%
“…Szura et al (2017) found stronger effects of Sesarma reticulatum with increased inundation. Likewise, Crotty et al (2017) indicated the potential interaction between future SLR and Sesarma reticulatum impacts on marshes, as did Raposa et al (2018b) based on increases in crab burrows during recent periods of higher water levels. Vu and Pennings (2017) noted that crab burrowing that increases creek size may actually have a positive effect on marsh integrity in the face of SLR, by increasing drainage.…”
Section: Crabs and Sea-level Risementioning
confidence: 97%
“…There is debate about how salt marshes will change in the Anthropocene; site-level research offers conflicting insight into the relationship of SLR to salt marsh loss such as multiple stressors leading to rapid loss [68] or only extreme SLR scenarios (30 cm) resulting in drowning [69]. Modeling studies suggest migration could lead to relative salt marsh stability [16].…”
Section: Salt Marsh Changementioning
confidence: 99%